Infelicities : representations of the exotic - Mason, Peter 1952- (Johns Hopkins University Press, 1998)
When European travelers went overseas in the sixteenth century, they encountered unfamiliar lands, peoples, and sights. These travelers had to re-present these encounters to Europeans for whom they stood for the unfamiliar -- the "exotic." But the exotic, according to Peter Mason, is not something that exists prior to its "discovery." Rather, he points out, it is the very act of "discovery" that produces the exotic as such.\In Infelicities Peter Mason explores the texts, paintings, drawings, photographs, and museum displays in which the exotic has been represented from the early modern period to the present. He describes the unique iconography that Europeans developed to represent the exotic and the means they employed to display it once artifacts were brought to Europe. In both instances, the exotic object is taken out of its original context and given a meaning and significance it never had; this new meaning and significance, Mason argues, are derived from the imposition of European cultural values and the need to recontextualize the object in a European setting. \To differentiate the "exotic" from the "other," Mason says that in understanding the "other" there is engagement and interchange; in encountering the "exotic" it is a one-sided effort at understanding: the exotic object never gives up its meaning. The title of the book, Infelicities, comes from philosopher J. L. Austin, who used the term to refer to what happens when something goes wrong on the occasion of an act of utterance. For Mason, this "doctrine of infelicities" seems applicable to European encounters with the exotic and the efforts to represent thoseencounters.